Chemical traits alteration of an acid soil by lime and recycling paper residue application - Balbinot Junior, Alvadi Antonio; Tôrres, André Nunes Loula; Fonseca, José Alfredo da; Teixeira, João Ribeiro; Neves, Cristiano Nunes (Revista de Ciências Agroveterinárias, 2006)
The recycling paper process generates residues that are usually placed in embankments. However, these residues present some constituents that can correct soil acidity and act as a source of nutrients, such as calcium. On the other hand, these residues also have heavy metals, which can cause negative environmental impacts. This work aimed to evaluate the effects of doses of lime and two kinds of recycling paper industry residues on the pHwater; pHSMP; levels of P, K, M.O., Al, Ca, Mg, Al+H; CTC; saturation by bases and by Al; Ca/Mg ratio; and levels of S, Zn, Cu, B, Mn, Fe, Hg, Pb, Ni, Cd and Cr. The lime and recycling paper residues corrected soil acidity, as well as modified significantly other soil chemical characteristics. The soil K levels were reduced by recycling paper residue application. Conversely, the application of recycling paper industry residues didn’t increase the soil heavy metals levels.